Teaching reading : effective schools, accomplished teachers - Taylor, Barbara M.; Pearson, P. David (L. Erlbaum Associates, 2002)
This work looks at large scale studies that have recently examined characteristics of effective schools and teachers, and provides case studies of five schools in which children are achieving at high levels in reading. It also deals with case studies of effective teachers of reading.